An Analysis of the Sandobatu Tradition in Compong Village, Sidenreng Rappang Regency: A Case Study of Masara Culture - Muh Yasir; Buhari; Sam Hermansyah; Ibrahim Manda (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research investigates the Sandobatu tradition in Compong Village, Sidenreng Rappang Regency, with a specific focus on its significance in preserving Masara culture. Utilizing a qualitative research approach, the study examines the role of traditional leaders in maintaining this cultural heritage and fostering a sense of identity among the community. The findings reveal that while traditional leaders actively promote and uphold the Masara traditions, the younger generation faces challenges in preserving them due to the growing influence of globalization and modern technology. This shift has led to a decline in cultural understanding and engagement among younger members of the community. In response, efforts have been made to educate the youth on the importance of these traditions through cultural discussions and interactive learning activities. Additionally, the study underscores the necessity of documenting and digitizing Masara rituals to ensure their longevity and accessibility for future generations. Preserving these traditions is crucial for maintaining the cultural integrity of the community and strengthening intergenerational connections.